RecA and RadA Proteins of Brucella abortus Do Not Perform Overlapping Protective DNA Repair Functions following Oxidative Burst - Roux, Christelle M.; Booth, Natha J.; Bellaire, Bryan H.; Gee, Jason M.; Roop, R. Martin II; Kovach, Michael E.; Tsolis, Renee M.; Elzer, Philip H.; Ennis, Don G. (East Carolina University, 2006)
Very little is known about the role of DNA repair networks in Brucella abortus and its role in pathogenesis. We investigated the roles of RecA protein, DNA repair, and SOS regulation in B. abortus. While recA mutants in most bacterial species are hypersensitive to UV damage, surprisingly a B. abortus recA null mutant conferred only modest sensitivity. We considered the presence of a second RecA protein to account for this modest UV sensitivity. Analyses of the Brucella spp. genomes and our molecular studies documented the presence of only one recA gene, suggesting a RecA-independent repair process. Searches of the available Brucella genomes revealed some homology between RecA and RadA, a protein implicated in E. coli DNA repair. We considered the possibility that B. abortus RadA might be compensating for the loss of RecA by promoting similar repair activities. We present functional analyses that demonstrated that B. abortus RadA complements a radA defect in E. coli but could not act in place of the B. abortus RecA. We show that RecA but not RadA was required for survival in macrophages. We also discovered that recA was expressed at high constitutive levels, due to constitutive LexA cleavage by RecA, with little induction following DNA damage. Higher basal levels of RecA and its SOS-regulated gene products might protect against DNA damage experienced following the oxidative burst within macrophages. Originally published Journal of Bacteriology, Vol. 188, No. 14, July 2006
Keywords: Brucella abortus; RecA; RadA; DNA repair